THE IMPORTANCE OF DIFFUSION WEIGHTED MAGNETIC RESONANCE IMAGING IN DIFFERENTIATION OF MALIGNANT AND BENIGN OVARIAN LESIONS - Lukač, Sonja; Kojić, Marina; Stojanović, Sanja (Medicinski podmladak, 2019)
Introduction: Ovarian cancer is the first on the list of mortality among all female genital cancers. However, there is no successful screening program for ovarian cancer detection. MRI has an important role in diagnostics of adnexal tumor with female patients. The use of diffusion weighted MRI (DWI) is getting more significant to help differentation benign and malignant ovarian lesions. Goals: Value Evaluation of ADC coefficient values in differentiation between benign and mignant ovarian lesions; correlation of ovarian and uterus ADC coefficient values in groups of female patients with or without malignant ovarian lesions. Materials and methods: The research has been conducted between the years of 2014 and 2017, as a retrospective clinical study in Radiology center of Clinical Centar of Vojvodina in Novi Sad. 45 female patients have been selected and sorted into 3 groups; First group has benign ovarian lesions, the second group malignant ovarian lesions and the third group with no ovarian lesions. ADC coefficient level has been measured on all the patients in three different places on the lesion itself, while patients with no lesions had their normal tissue measured. The ADC coefficient level has also been measured on the normal part of each patient’s uterus. Results: The analysis and comparison of ADC coefficient between the three groups point out on statistical significant difference of values of ADC coefficient with patients with malignant lesions and ones with benign or no lesions at all. Conclusion: The ADC coefficient level has been recognized as a very relevant detector of malignant ovarian lesions during MRI examination. Key words: Magnetic resonance imaging (MRI), ADC coefficient, malignant ovarian lesions